Simulator Respon Alat Sensor Water Flow Berbasis Android - Anita Rahmawati (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2019)
This irrigation design was made to optimize the provision of water to plants. The system works with an automatic control system, so it is expected to be able to control the surface of the ground water to remain stable. Then this simulator tool also functions to increase productivity and efficiency of use, especially irrigation water in rice fields. Automatic irrigation tools that have been designed using NoDeMCU as a microcontroller are connected directly to Android, this aims to make it easier to monitor and control water use remotely.